Talent management challenges during COVID-19 and beyond: Performance management to the rescue. Issue 3 (July 2021) - Aguinis, Herman; Burgi-Tian, Jing
The COVID-19 pandemic has resulted in significant talent management challenges including (a) hiring freezes and layoffs; (b) salary freezes, canceled bonuses, and pay reductions; (c) how work is done (i.e., teleworking); and (d) increased employee stress and burnout. Also, COVID-19 has made it evident that many organizations do not implement state-of-the-science performance management systems and, instead, have just performance appraisal systems that typically involve a once-a-year evaluation and review, little effort to provide feedback and coaching on an ongoing basis, little alignment between employee performance and the organization's strategic goals, a focus on past performance only, and ownership by the human resources function instead of those rating and being rated. Thus, the lack of value contributed by the usual performance evaluation and review process is the reason why so many organizations are postponing or even completely discontinuing performance evaluations. We argue that when implemented using evidence-based recommendations, performance management (rather than appraisal) serves important administrative, strategic and communication, developmental, organizational maintenance, and documentation purposes and therefore can be particularly useful in addressing contemporary talent management challenges. We offer five recommendations on how to adapt and improve performance management that will help organizations navigate crises like COVID-19 and, just as importantly, allow them to thrive after the crisis is over: (1) measure results in addition to behaviors, (2) measure adaptive performance, (3) conduct stay interviews to retain top performers, (4) implement a multisource performance management system, and (5) collect and use performance promoter scores. JEL CLASSIFICATION: J5 Labor–Management Relations, Trade Unions, and Collective Bargaining; M1 Business Administration; M5 Personnel Economics